Studi Deskriptif Pemberian Pekerjaan Rumah Bagi Siswa Dalam Pelajaran Seni Budaya Di Kelas VII SMP Negri 3 Painan Kabupaten Pesisir Selatan - Riri Febrianti; Yos Sudarman (FBS Universitas Negeri Padang, 2020)
This study aims to explain two things, about (1) the implementation of giving homework in the field of theory (using LKS) in arts and culture lessons (music) for Class VII students of SMP 3 Painan, Pesisir Selatan Regency; and (2) Implementation of homework assignments in the field of practice (without LKS) on arts and culture lessons (music) for Class VII students of Painan 3 South Pesisir Regency. This type of research is a qualitative research with a descriptive analysis method, the research produced will provide a clear picture of the object under study with various points of view and various explanations. Data collection techniques by observation, interview notes, documentation notes and study literature notes. Data analysis techniques are collecting data, identifying data, classifying data, describing data, and drawing final conclusions. After collecting the data, the results obtained that the results of the study found problems in giving assignments by the teacher to students in music culture and art lessons in class VII, which is less effective, and not balanced. Homework assignments in the form of musical art practice exercises (without worksheets) performed outside the classroom by students have less portions, compared to assigning theoretical work (using worksheets) done by students individually or in groups. However, at the next learning meeting in class, the teacher asked questions and collected the results of the music practice as evidence of homework in the form of practice already carried out. While homework in the form of theory that students do with worksheets has never been asked or questioned by the teacher. So the results of this study show that there are two opposites, where the results of homework without worksheets carried out by students practicing at home are more questioned by the teacher, while homework with worksheets done by students is not discussed more.